Everolimus in advanced, progressive, well‐differentiated, non‐functional neuroendocrine tumors: RADIANT‐4 lung subgroup analysis. Issue 1 (9th November 2017) - Fazio, Nicola; Buzzoni, Roberto; Delle Fave, Gianfranco; Tesselaar, Margot E.; Wolin, Edward; Van Cutsem, Eric; Tomassetti, Paola; Strosberg, Jonathan; Voi, Maurizio; Bubuteishvili‐Pacaud, Lida; Ridolfi, Antonia; Herbst, Fabian; et al.
Abstract : In the phase III RADIANT‐4 study, everolimus improved median progression‐free survival (PFS) by 7.1 months in patients with advanced, progressive, well‐differentiated (grade 1 or grade 2), non‐functional lung or gastrointestinal neuroendocrine tumors (NETs) vs placebo (hazard ratio, 0.48; 95% confidence interval [CI], 0.35‐0.67; P < .00001). This exploratory analysis reports the outcomes of the subgroup of patients with lung NETs. In RADIANT‐4, patients were randomized (2:1) to everolimus 10 mg/d or placebo, both with best supportive care. This is a post hoc analysis of the lung subgroup with PFS, by central radiology review, as the primary endpoint; secondary endpoints included objective response rate and safety measures. Ninety of the 302 patients enrolled in the study had primary lung NET (everolimus, n = 63; placebo, n = 27). Median PFS (95% CI) by central review was 9.2 (6.8‐10.9) months in the everolimus arm vs 3.6 (1.9‐5.1) months in the placebo arm (hazard ratio, 0.50; 95% CI, 0.28‐0.88). More patients who received everolimus (58%) experienced tumor shrinkage compared with placebo (13%). Most frequently reported (≥5% incidence) grade 3‐4 drug‐related adverse events (everolimus vs. placebo) included stomatitis (11% vs. 0%), hyperglycemia (10% vs. 0%), and any infections (8% vs. 0%). In patients with advanced, progressive, well‐differentiated, non‐functional lung NET, treatment with everolimus was associated with a median PFS improvement of 5.6 months, with a safety profile similar to that of the overall RADIANT‐4 cohort. These results support the use of everolimus in patients with advanced, non‐functional lung NET. The trial is registered with ClinicalTrials.gov (no. NCT01524783). Abstract : This exploratory subgroup analysis of the RADIANT‐4 study is the first study to demonstrate that everolimus, a systemic targeted therapy, was associated with clinically meaningful improvement of 5.6 months in the median progression‐free survival with 50% reduction in risk of disease progression or death compared to placebo, in patients with advanced, progressive, well‐differentiated, nonfunctional lung neuroendocrine tumors (NET). This is the largest lung NET population ever included in a phase 3 trial.